(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Urban spatial transformation in Indonesia is inseparable from the enduring influence of colonialism, which has significantly contributed to the reconfiguration of urban spatial structure, functional organization, and spatial meaning. The Alun-alun, as a fundamental component of Javanese urban form, has experienced substantial transformation through the continuous negotiation between indigenous value systems and colonial interventions in spatial governance. This study seeks to investigate the spatial transformation of the Magelang Alun-Alun, to analyze the dynamics of local–colonial power relations embedded within its spatial restructuring, and to interpret the evolving meanings of space through an urban morphological lens. This research is situated within a qualitative-historical framework, utilizing archival investigation, field-based observation, and semi-structured interviews as primary methods of data collection. The analytical process is structured through spatial-historical analysis, examination of power relations, and biographical interpretation of space, enabling the identification of multilayered transformations in both spatial configuration and spatial meaning. The findings reveal that the Magelang Alun-Alun has undergone a significant transition from a cosmologically oriented space, reflecting the integration of indigenous authority systems and spiritual cosmology, into a more formally structured administrative space under colonial governance. This transformation not only redefined the physical spatial organization but also reconstructed the functional role and symbolic meaning of the Alun-Alun as an instrument of power representation and territorial control. Nevertheless, certain indigenous spatial elements persisted despite colonial restructuring, resulting in a hybridized spatial configuration that reflects both continuity and change. This study demonstrates that the Magelang Alun-Alun can be interpreted as a palimpsestic urban space, in which multiple historical layers coexist and interact to produce complex spatial meanings. The contribution of this research lies in the integration of urban morphological analysis with the study of power relations and spatial meaning, thereby offering a more comprehensive and critical understanding of colonial urban spatial transformation processes.